2009
DOI: 10.1111/j.1574-6968.2008.01406.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic islands ofPseudomonas aeruginosa

Abstract: Key to Pseudomonas aeruginosa’s ability to thrive in a diversity of niches is the presence of numerous genomic islands that confer adaptive traits upon individual strains. We reasoned that P. aeruginosa strains capable of surviving in the harsh environments of multiple hosts would therefore represent rich sources of genomic islands. To this end, we identified a strain, PSE9, that was highly virulent in both animals and plants. Subtractive hybridization was used to compare the genome of PSE9 to the less virulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 42 publications
1
60
0
5
Order By: Relevance
“…Lee et al (2006) have reported pathogenicity-related genes, the presence or absence of which do not correlate directly with degree of virulence, suggesting virulence is more complex than simple autonomous functioning of virulence genes. Strain-variable virulence-associated genes have been reported within genomic islands of P. aeruginosa (Battle et al, 2009). These mobile genetic elements can contribute to virulence in a combinatorial manner with other accessory genome 'modules', resulting in strain-specific virulence (Lee et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (2006) have reported pathogenicity-related genes, the presence or absence of which do not correlate directly with degree of virulence, suggesting virulence is more complex than simple autonomous functioning of virulence genes. Strain-variable virulence-associated genes have been reported within genomic islands of P. aeruginosa (Battle et al, 2009). These mobile genetic elements can contribute to virulence in a combinatorial manner with other accessory genome 'modules', resulting in strain-specific virulence (Lee et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…regulador transcricional dependente de zinco e uma proteína similar a TraY (fator acessório necessário para ligação da relaxase no plasmídeo F) de Cupriavidus metallidurans (Battle, et al 2009). …”
Section: Pagi-8 Esta Ilha Genômica Carrega O Elemento De Inserção Isunclassified
“…PAGI-9 e -10 são formadas por apenas um único gene cada, ambos relacionados a família Rhs que são elementos acessórios presente em E. coli, relacionada com biogênese do envelope celular e membrana externa, e PAGI-11 é uma região 28 de 2 kb que não contém nenhum gene predito e que não está presente em PSE9 e sim em PAO1 (McNulty, et al 2006;Battle, et al 2009). …”
Section: Pagi-8 Esta Ilha Genômica Carrega O Elemento De Inserção Isunclassified
See 2 more Smart Citations